Plessy v Ferguson and the literary imagination - B. Thomas (Law Text Culture, 1997)
On 7 June 1892, Homer Plessy was arrested for violating Section 2 of Act 111 passed by the Louisiana Legislature in 1890. The law called for 'equal but separate accommodations for the white and colored races' on all passenger railways within the state. Plessy's arrest was part of a planned challenge to the law by New Orleans blacks, who fanned a committee of protest. In September 1891 the committee had contacted the white lawyer Albion Winegar Tourgee.